Rough magic : making theatre at the Royal Shakespeare Company - Adler, Steven, 1953- (Southern Illinois University Press, 2001)
This book provides a thorough analysis of the many strands of theatrical activity on both sides of the footlights that coalesce in the artistic vigor of the Royal Shakespeare Company. Adler traces the company's evolution from its origins in 1879 as a week-long festival presented by Stratford-upon-Avon as a birthday homage to its native son, to its current incarnation as one of the world's most distinguished institutional theatres. The author probes the aspirations and achievements of the RSC's four successive artistic directors: Peter Hall, Trevor Nunn, Terry Hands, and Adrian Noble. He offers a comprehensive view of the design and aesthetics of the RSC's five theatres in Stratford and London, and explores the intricate process of crafting a repertoire at home and on tour that responds to the needs of the artists as well as the demands of the box office. Richly illustrated with vivid photographs, Rough magic examines the fusion of artistic vision and theatrical energy that make invigorating theatre at the RSC.